Medical applications of EPR - Eichhoff, Uwe; Höfer, Peter (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Selected applications of continuous-wave EPR in medicine are reviewed. This includes detection of reactive oxygen and nitrogen species, pH measurements and oxymetry. Applications of EPR imaging are demonstrated on selected examples and future developments to faster imaging methods are discussed.